1990
DOI: 10.1126/science.248.4951.57
|View full text |Cite
|
Sign up to set email alerts
|

Physical Conditions at the Base of a Fast Moving Antarctic Ice Stream

Abstract: Boreholes drilled to the bottom of ice stream B in the West Antarctic Ice Sheet reveal that the base of the ice stream is at the melting point and the basal water pressure is within about 1.6 bars of the ice overburden pressure. These conditions allow the rapid ice streaming motion to occur by basal sliding or by shear deformation of unconsolidated sediments that underlie the ice in a layer at least 2 meters thick. The mechanics of ice streaming plays a role in the response of the ice sheet to climatic change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
310
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 439 publications
(334 citation statements)
references
References 41 publications
21
310
2
1
Order By: Relevance
“…The underlying questions are how strongly subglacial geology influences the transition from slow flow via internal deformation to streaming ice flow due to rapid basal motion, and how far the potential for ice streaming extends into the inland ice reservoir of West Antarctica. Previous work has shown that streaming ice in West Antarctica is underlain by sedimentary packages Rooney et al, 1991;Smith, 1997;Anandakrishnan et al, 1998;Bell et al, 1998;Doake et al, 2001;Studinger et al, 2001;Anandakrishnan, 2003;Vaughan et al, 2003], that a soft bed is present immediately beneath the ice to allow rapid basal motion [Engelhardt et al, 1990;Engelhardt and Kamb, 1998;Tulaczyk et al, 1998;Kamb, 2001], and that subglacial sediments appear to shape the inland extent of streaming ice flow [Anandakrishnan et al, 1998;Bell et al, 1998;Blankenship et al, 2001;Studinger et al, 2001]. However, much geological heterogeneity has been found across West Antarctica, indicating that the mechanisms for producing streaming ice flow may vary.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The underlying questions are how strongly subglacial geology influences the transition from slow flow via internal deformation to streaming ice flow due to rapid basal motion, and how far the potential for ice streaming extends into the inland ice reservoir of West Antarctica. Previous work has shown that streaming ice in West Antarctica is underlain by sedimentary packages Rooney et al, 1991;Smith, 1997;Anandakrishnan et al, 1998;Bell et al, 1998;Doake et al, 2001;Studinger et al, 2001;Anandakrishnan, 2003;Vaughan et al, 2003], that a soft bed is present immediately beneath the ice to allow rapid basal motion [Engelhardt et al, 1990;Engelhardt and Kamb, 1998;Tulaczyk et al, 1998;Kamb, 2001], and that subglacial sediments appear to shape the inland extent of streaming ice flow [Anandakrishnan et al, 1998;Bell et al, 1998;Blankenship et al, 2001;Studinger et al, 2001]. However, much geological heterogeneity has been found across West Antarctica, indicating that the mechanisms for producing streaming ice flow may vary.…”
Section: Introductionmentioning
confidence: 99%
“…These fast flowing ice streams are conspicuous in satellite images [Stephenson and Bindschadler, 1990;Bindschadler, 1991, 1993;Hodge and Doppelhammer, 1996] and ice velocity maps [Joughin et al, 1999[Joughin et al, , 2002, with well-defined lateral margins, and extend several hundred kilometers into the ice sheet. Seismic imaging Rooney et al, 1991;Anandakrishnan et al, 1998] and borehole analysis [Engelhardt et al, 1990;Tulaczyk et al, 1998;Kamb, 2001] have shown that, in places, streaming ice is coincident with subglacial sediments. The upper meters of these sediments are soft till, with the potential for active deformation Engelhardt et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subglacial geology has been recognised as a strong influence on some ice streams, where their activity is affected by the underlying topography, deeper structure (Anandakrishnan et al, 1998), and geology at the ice-bed interface . Many ice streams are known to be underlain by a layer of soft, dilatant, deformable sediments which facilitates fast ice motion and high ice discharge (Boulton and Hindmarsh, 1987;Blankenship et al, 1987;Engelhardt et al, 1990;Kamb, 2001). Outside of these streams, regions of slower ice flow often correlate with rugged beds characterised by sedimentary rocks or crystalline bedrock.…”
Section: Introductionmentioning
confidence: 99%